Implementasi Gaya Belajar VAK Berdasarkan Tipe Kepribadian Hippocrates-Galenus Mahasiswa Semester VI Tahun Akademik 2022/2023 STAB Kertarajasa - Yayuk; Herman; Amita Wardhani (Jounal Nyanadassana, 2023)
The background of this research is the existence of personality differences that determine the less effective character and learning style so that it becomes a factor in underachievement. This study aims to explain the implementation of the VAK learning style (Visual, Auditory, and Kinesthetic) based on the Hippocrates-Galenus Personality for Semester VI Students of the 2022/2023 Academic Year STAB Kertarajasa. This research is qualitative research with a case study research design. In this study, differences were found the use of the VAK learning style, namely 1) individuals with Sanguinis one personality, A2, used visual and kinesthetic learning styles, but kinesthetics was only used at complicated levels, while A3 used a less effective learning style; 2) individuals with Choleric personality use mixed learning styles, namely visual, auditory, and kinesthetic at the same time, with a visual tendency, but they still want to try using auditory and kinesthetic; 3) individuals with Melancholic personality use visual kinesthetic and auditory and kinesthetic visual learning styles; individuals with a melancholic personality always try to increase knowledge; and 4) individuals with phlegmatic personalities use visual and auditory learning styles, individual one, D6, changes his learning style when entering lectures while the other individual, D7, adapts according to the situation.